2016
DOI: 10.3892/etm.2016.3410
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of naringin against ankylosing spondylitis via ossification, inflammation and oxidative stress in mice

Abstract: Abstract. Naringin is an abundant flavanone in pomelo, grapefruit as well as lime and its variants, has been shown to exhibit certain antioxidative, anti-inflammatory, anti-cancer and hypoglycemic effects. The aim of the current study was to evaluate the protective effects of naringin against ankylosing spondylitis (AS) and to elucidate the potential underlying mechanism. Firstly, a mouse model of ankylosing spondylitis (AS) was established. Next, osteocalcin (OC), alkaline phosphatase (ALP) and triglyceride (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Considering the delay in diagnosis and insufficient effective therapeutic options available, identification and development of more effective compounds become inevitable. Recently, much research has been focused on the efficacy of plant-derived compounds in AS [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the delay in diagnosis and insufficient effective therapeutic options available, identification and development of more effective compounds become inevitable. Recently, much research has been focused on the efficacy of plant-derived compounds in AS [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several plant-derived compounds have been shown to possess neuroprotective effects [ 5 , 23 , 24 ]. Punicalagin (2,3-hexahydroxydiphenoyl-gallagyl-D-glucose) is an ellagitannin and is the major bioactive polyphenol widely present in pomegranates.…”
Section: Introductionmentioning
confidence: 99%
“…NG is a naturally occurring phytochemical commonly found in grapefruit juice with a number of health benefits [41]. It has been much explored by different research groups for its capability to ameliorate hazardous effects of various metals [42] as well as in different pathological conditions [43][44][45]. NG has been reported to mitigate cisplatin-induced OxiS and inflammatory response.…”
Section: Studies On Ameliorative Nature Of Ng Against Oxismentioning
confidence: 99%
“…Oral administration of NG (10, 20, and 40 mg/kg) to isoproterenol exposed Wistar rats showed a considerable decrease in the levels of lipid peroxidation products and improved the antioxidant status [47]. NG is known for its anti-inflammatory [46,[48][49][50] and antioxidative nature [43,45,51,52]. Arsenic-induced hepatic and renal toxicity are reported to be reduced by anti-inflammatory and antioxidative nature of NG [53].…”
Section: Studies On Ameliorative Nature Of Ng Against Oxismentioning
confidence: 99%
“…Naringin was used in a recent study that involved a mouse model of ankylosis spondylitis. Analysis of harvested tissues showed that flavonoid intraperitoneal administration attenuated the expression of proinflammatory cytokines [such as tumor necrosis factor (TNF)-α, interleukin (IL)-1β and IL-6] and inhibited the production of signal transducer and activator of transcription (STAT)3 and Janus kinase (JAK)2 (implicated in the sensitivity to this disease) in a dose-dependent manner[52]. In parallel, naringin also improved oxidative stress markers in treated mice by restoring the activity of superoxide dismutase, catalase and glutathione peroxidase in vivo.…”
mentioning
confidence: 99%